Influence of the Renewable and Non-Renewable Energy Consumptions and Real-Income on Environmental Degradation in Indonesia - Muchran, Muchran; Idrus, Arifin; Badruddin, Syamsiah; Tenreng, Mariana; Kanto, Muklis (International Journal of Energy Economics and Policy, 2020)
The purpose of this research is to determine the effects of the income (GDP), renewable-energy consumptions and the non-renewable energy consumptions over the (CO2) carbon dioxide emission for Indonesia by Kuznets Environmental Curve EKC) model for the time span of 1980 to 2018 period. The study uses the time series data so in order to check the order of integration of the variables, the Augmented Dickey-Fuller (ADF) and Phillips Perron (PP) unit root test have been applied. Furthermore, the study has used the ARDL methodology to estimate the cointegration in-between the model and also for long and short-run estimates of the model. ARDL Bound test confirms the cointegration among the CO2, income, energy consumption, renewable and nonrenewable energy consumption. Long-term estimates obtained from A.R.D.L. model show that increasing renewable energy consumptions reduces degradation of the environment while increasing nonrenewable energy consumptions boosts the level of CO2 emissions. GDP has a negative while the square of GDP has a positive impact on CO2 emission levels. Moreover, the E.K.C. assumption does not hold for Indonesia because the coefficient of income and income square are opposite, and the results of current studies are consistent and unbiased. This study suggested that in order to reduce the CO2 emissions Indonesian government needs to: adopt renewable energy resources, encourage the industries to adopt clean technology and renewable energies, and raise public-awareness of healthy ways of energy-consumptions. Keywords: Renewable energy, CO2 emissions, Environmental Kuznets Curve, Autoregressive-Distributed Lag JEL Classifications: O13, Q42, Q43 DOI: https://doi.org/10.32479/ijeep.10780